Cerebellum/liver index in pretherapeutic 18F-FDG PET/CT as a predictive marker of progression-free survival in follicular lymphoma treated by immunochemotherapy and rituximab maintenance. Issue 5 (4th February 2022) - Godard, François; Durot, Eric; Durot, Carole; Hoeffel, Christine; Delmer, Alain; Morland, David
Abstract : Abstract: The purpose of this study was to investigate the value of the "cerebellum/ liver index for prognosis" (CLIP) as a new prognostic marker in pretherapeutic 18 F-Fluorodeoxyglucose positron emission tomography ( 18 F-FDG PET) in patients with follicular lymphoma treated by immunochemotherapy and rituximab maintenance, focusing on progression-free survival (PFS). Clinicobiological and imaging data from patients with follicular lymphoma between March 2010 and September 2015 were retrospectively collected and 5-year PFS was determined. The conventional PET parameters (maximum standardized uptake value and total metabolic tumor volume) and the CLIP, corresponding to the ratio of the cerebellum maximum standardized uptake value over the liver SUVmean, were extracted from the pretherapeutic 18 F-FDG PET. Forty-six patients were included. Eighteen patients (39%) progressed within the 5 years after treatment initiation. Five-year PFS was 78.6% when CLIP was >4.0 and 42.0% when CLIP was <4.0 ( P  = .04). CLIP was a significant predictor of PFS on univariate analysis (hazard ratio 3.1, P  = .049) and was near-significant on multivariate analysis (hazard ratio 2.8, P  = .07) with ECOG PS as a cofactor. The CLIP derived from pretherapeutic 18 F-FDG PET seems to be an interesting predictive marker of PFS in follicular lymphoma treated by immunochemotherapy and rituximab maintenance. These results should be evaluated prospectively in a larger cohort.